BELAJAR DALAM SUASANA DESAIN YANG MENYENANGKAN - Jessica Giovani Wirantono; Freddy H. Istanto; Rani Prihatmanti (Universitas Ciputra Surabaya, 2016)
Lately, the development of interior design is growing rapidly. People have higher demand towards children interior because of higher purchasing power and they think children are their priority. As the side effect of AFTA, people are more into children design. It triggers the market in Indonesia to produce more and more of children design as the international market makes a great influence. The tenants from abroad causing the increase in demand of children interior design. The company is taking those opportunities to give the best solution on their children interior design. According to most of interior design company, they are focusing on the aesthetic without considering the growth of the children. JesGio Interior Architecture has the ability to indicate the greatness of the design and considering the development of the children, so that it will be a great investment. The company will give good services and trustworthiness to build a great relation with the customers. JesGio Interior Architecture is focusing on children project with a big hope to serve well our next generation. ABC CASTLE Child Development Center is one of the project created by JesGio Interior Architecture. ABC CASTLE has the combination of education purpose with entertainment. The concept will give the essence of learning and helpful in any kind of study.